Religion, Cognition, and Political Behavior: An Interdisciplinary Exploration of Faith-Based Polarization Mechanisms - Syahirul Alim (Peradaban Journal of Religion and Society, 2024)
Political polarization is a complex phenomenon with significant implications for democratic processes worldwide. This study investigates the cognitive mechanisms underlying political reinforcement learning and examines how environmental information influences political decision-making, resulting in diverse political behaviors and beliefs. The methodology employed encompasses descriptive analysis, systematic literature review, and content analysis. Data were sourced from various democratic countries to ensure a comprehensive and diverse perspective. Key findings indicate that both traditional and social media significantly shape political opinions, while cognitive biases and political motivations can lead to divergent interpretations of identical facts, culminating in polarized beliefs. Interventions that enhance cognitive flexibility and metacognitive insight, as well as those promoting civil discourse and reducing intergroup anxiety, were found to be effective in mitigating political polarization. This research provides valuable insights into the cognitive and social dynamics underlying political polarization and proposes strategies to reduce polarization and strengthen democratic institutions. Future research should prioritize the empirical validation of these models and the testing of interventions across diverse cultural and political contexts.